The THE RELATIONSHIP BETWEEN THE INTENSITY OF SOCIAL MEDIA USE AND THE LEVEL OF ANXIETY AND DEPRESSION IN MEDICAL STUDENTS - Natasya, Amanda Michelle; Lesmana, Cokorda Bagus Jaya; Aryani, Luh Nyoman Alit; Wardani, Ida Aju Kusuma; Wardani, Ida Aju Kusuma (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i3.P15, 2025)
Technology is becoming more advanced and quick not only has a positive effect on humans but also a negative impact on humans, especially students. We conducted this study to investigate the relationship between the intensity of social media use and the level of anxiety and depression among students in the Udayana University Medical Education Study Program, Class of 2021. This correlational analytical observational study aimed to examine variable relationships using purposive sampling of 94 students from the Udayana University Medical Education Study Program, Class of 2021. Data were collected via online questionnaires assessing social media use intensity, anxiety levels, and depression levels, and analyzed using SPSS software. The results showed that the intensity of social media use with anxiety level showed p = 0.277 and the intensity of social media use with depression level showed p = 0.227. The relationship between the intensity of social media use and the level of anxiety and depression in students of the 2021 Udayana University Medical Education Study Program shows that there is no statistically significant relationship. Therefore, it is vital to conduct research on additional variables that are related and can affect the level of anxiety and level of depression that have not been studied in this study and further research based on more specific types of social media.